EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN DI SMP NEGERI 2 TARAKAN PADA MASA PANDEMI COVID-19 - MOCHAMMAD MACHFUD (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2021)
One of the important factors in learning activities is the existence of learning media that attracts the attention of students. Media is an intermediary tool between educators and students and is very supportive in the delivery of learning material to make it easier to learn and understand it. The outbreak of the Covid-19 pandemic in Indonesia has an impact on the Indonesian education process. Educational activities must be carried out online, students and teachers do not meet each other. So that the learning media that is an alternative for educators during the Covid-19 pandemic is the use of learning video media. The purpose of this study was to see the effectiveness of using video media in learning at SMP Negeri Tarakan during the Covid-19 pandemic based on the educator's perspective. The methodology used in this study is descriptive quantitative with an instrument in the form of a questionnaire given to teachers at SMP Negeri 2 Tarakan in October 2021. The results show that the implementation of learning during the Covid-19 pandemic using learning video media by subject teachers has goes well. Media in the form of learning videos is effectively used during the Covid-19 pandemic, because it makes it easier for educators to teach material that needs explanation and makes it easier for students to understand learning material. ABSTRAKSalah satu faktor penting dalam kegiatan pembelajaran adalah adanya media pembelajaran yang menarik perhatian peserta didik. Media merupakan alat perantara antara pendidik dengan peserta didik dan sangat menunjang dalam penyampaian materi pembelajaran agar lebih mudah untuk mempelajari dan memahaminya. Mewabahnya pandemi Covid-19 di Indonesia memberikan pengaruh bagi proses pendidikan Indonesia. Kegiatan pendidikan harus dilaksanakan dengan daring peserta didik dan guru tidak saling bertemu. Sehingga media pembelajaran yang menjadi alternatif pendidik saat pandemi Covid-19 adalah penggunaan media video pembelajaran. Tujuan dari penelitian ini adalah untuk melihat efektivitas penggunaan media video dalam pembelajaran di SMP Negeri Tarakan selama masa pandemi Covid-19 berdasarkan perspektif pendidik. Metodologi yang digunakan pada penelitian ini adalah deskriptif kuantitatif dengan instrumen berupa angket yang diberikan kepada guru-guru di SMP Negeri 2 Tarakan pada bulan Oktober 2021. Hasil penelitian memperlihatkan bahwa pelaksanaan pembelajaran pada masa pandemi Covid-19 dengan menggunakan media video pembelajaran oleh guru mapel telah berjalan dengan baik. Media berupa video pembelajaran efektif digunakan pada masa pandemi Covid-19, karena memudahkan pendidik dalam mengajarkan materi yang perlu adanya penjelasan serta memudahkan peserta didik memahami materi pembelajaran.